Difference and environmental drivers of bacterial communities on wall paintings of the Maijishan and Mogao Grottoes, China - Ma, Wenxia; Chen, Qiqi; Wu, Fasi; He, Dongpeng; Duan, Yulong; Yue, Yongqiang; Gu, Ji-Dong; Yang, Xiaoyan; Feng, Huyuan (Frontiers in Microbiology, 2025)
The Maijishan and Mogao Grottoes, both UNESCO World Heritage Sites along the Silk Road, are increasingly threatened by microbial biodeterioration. To characterize bacterial communities of different microbial damages on wall paintings and identify environmental drivers, we combined high-throughput DNA/RNA sequencing with microenvironmental monitoring and conducted a cross-site comparison. At Maijishan, bacterial communities associated with black and white mycelia showed no significant compositional differences within the same cave but varied markedly between caves, indicating site-specific community assembly. Actinobacteria (>50%), particularly Pseudonocardia and Actinomycetospora, predominated, while RNA-based analysis revealed active populations of Escherichia and Stenotrophomonas, likely introduced via exogenous contamination from animal activities. In contrast, black spots from the Mogao Grottoes were dominated by Actinobacteria, Firmicutes, and Proteobacteria, with Rhodococcus as a core genus. No core bacterial OTUs were shared between the sites, suggesting strong microenvironmental filtering. Multivariate analysis identified substrate properties (total organic carbon, total nitrogen, pH) and microclimatic fluctuations (diurnal temperature/humidity ranges) as critical drivers. Maijishan’s persistently humid conditions (RH > 70% for over 180 days/ year) favored Actinobacteria proliferation, whereas Mogao’s arid climate (RH < 70% for over 240 days/year) selected for xerotolerant Firmicutes. These results reveal distinct site-specific microbial colonization patterns and provide a scientific basis for targeted conservation strategies to mitigate microbial damage and preserve these invaluable wall paintings.